Alternative Procedures and Quality of Financial Report Audit Results in the Era of the Covid 19 Pandemic - Rivcy Jassin; Jantje. J Tinangon; Novi Swandari Budiarso (Journal of Business and Management Review, 2022)
This study aims to determine the implementation, constraints, efforts to overcome obstacles, and the result audit quality when using the alternative procedures for auditing local government financial report (LKPD) which is conducted by The Representative of Audit Board Indonesia in North Sulawesi Province (BPK of North Sulawesi) in the Covid 19 Pandemic Era.This study uses a qualitative method with a case study approach. The data was collected through interviews and documentation studies. The results showed that The Representative of Audit Board Indonesia in North Sulawesi Province had implemented alternative procedures for auditing local government financial report by preparing adequate regulations and policies. Improving the competence of the auditor through training, workshops, socialization, dissemination, knowledge transfer forum, compiling Frequently Asked Questions (FAQ), and making messenger group. In addition, preparing an audit program that accommodates alternative procedures in accordance with existing regulations, developing audit strategies and alternative procedures through the utilization of the Internal Government Supervisory Apparatus (APIP), utilizing information technology, and tiered reviews. Problem that faced in implementing alternative procedures are the lack of local government commitment in preparing a stable internet network, supporting devices, personnel in related office, the number of competent APIP teams as needed. Lack experience auditor does not have the same knowledge about the details of steps and supporting documents. These issues can be overcome through increasing local government commitment, the number competence APIP team as needed, and the competence of new auditor of Audit Board Indonesia.The quality of audit results in the era of the Covid 19 pandemic has fulfilled the requirement with indicators of quality control and quality assurance achievements, the achievement of the auditee satisfaction index for LKPD examinations, the achievement of timely submission of LKPD audit report (LHP LKPD), and the achievement of the percentage of lawsuits against LHP won by the Audit Board of Indonesia